2005
DOI: 10.1088/0953-8984/17/30/002
|View full text |Cite
|
Sign up to set email alerts
|

Ab initioelectronic and structural properties of clean and hydrogen saturated β-SiC(100)(3 × 2) surfaces

Abstract: This paper deals with ab initio calculations relating to the atomic and electronic structure of the β-SiC(100)(3 × 2)-H surface. The results lead to the interpretation that electronic states associated with H atoms are responsible for a metallic behaviour, when saturation in the H deposition on the clean β-SiC(100)(3 × 2) is effected, a feature observed experimentally by Derycke et al. Although confirming the experimentally observed electronic behaviour, the present results differ as regards the H atom positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
3
7
0
Order By: Relevance
“…This is in clear contradiction to what was observed for the SD model and also to the 'normal' behaviour for this kind of adsorption, where the tendency is to 'clean the gap' by removal of the dangling bonds. However, this behaviour of our calculated results is similar to that observed for the silicon terminated β-SiC(100)(3 × 2) [13,23].…”
Section: Electronic Featuressupporting
confidence: 88%
See 1 more Smart Citation
“…This is in clear contradiction to what was observed for the SD model and also to the 'normal' behaviour for this kind of adsorption, where the tendency is to 'clean the gap' by removal of the dangling bonds. However, this behaviour of our calculated results is similar to that observed for the silicon terminated β-SiC(100)(3 × 2) [13,23].…”
Section: Electronic Featuressupporting
confidence: 88%
“…However, it was reported that such hydrogen adsorption may also lead to metallization under certain conditions [13]. This experimental observation for the β-SiC(100)(3 × 2) surface has motivated theoretical calculations for interpreting this unusual phenomenon [21][22][23]. These results have suggested the possibility of exploring a similar phenomenon coming from hydrogen adsorbed on other β-SiC(100) reconstructed surfaces, such as the carbon terminated β-SiC(100)-c(2 × 2).…”
Section: Introductionmentioning
confidence: 98%
“…This study was based on electronic and vibrational properties probed by both advanced experimental techniques, namely SR-PES and high-resolution electron energy losses spectroscopy (HREELS), and by state-of-the-art theoretical calculations [8]. The vibrational modes from the HREELS measurements [8] are in excellent agreement with previous IRAS measurements [7] and revealed the lack of any vibrational mode arising from H or D atoms in a bridge-bond between Si atoms in the third plane, as favored by earlier theoretical investigations [1,[9][10][11][12]. In addition, such a bridge-bond position for H between two Si atoms in the third plane is also inconsistent with synchrotron radiationbased core-level photoemission spectroscopy (SR-CL-PES) experiments indicating an asymmetric charge transfer in the third atomic plane [13].…”
supporting
confidence: 68%
“…The first one was assigned to Si-H bonds at the Si first layer while the second was assigned to Si-H bonds with the Si atom directly bonded to a C atom ͑i.e., third-layer Si atoms͒. This proposal was followed by several DFT calculations 33-36 that showed that this structure is not stable; instead, an alternative model was proposed in which the H atoms on the third layer occupy bridge positions on top of the third-layer Si dimer, [33][34][35][36][37] ͓i.e., a B͑2,0,2͒ model in our notation͔; some of these calculations, however, already noted that for this coverage the D͑4,0,0͒ model was clearly more stable than the B͑2,0,2͒ ͑Refs. 33 and 34͒ ͑see also Table I͒. Recently, an alternative explanation has been proposed based in DFT calculations of ϳ50 surface structures with 2-14 hydrogen atoms per 3 ϫ 2 unit cell.…”
Section: B Hydrogen-induced Metallization Of Sic(100)-3 ãmentioning
confidence: 99%